2022
DOI: 10.1126/sciadv.abj8360
|View full text |Cite
|
Sign up to set email alerts
|

The glucocorticoid receptor associates with the cohesin loader NIPBL to promote long-range gene regulation

Abstract: The cohesin complex is central to chromatin looping, but mechanisms by which these long-range chromatin interactions are formed and persist remain unclear. We demonstrate that interactions between a transcription factor (TF) and the cohesin loader NIPBL regulate enhancer-dependent gene activity. Using mass spectrometry, genome mapping, and single-molecule tracking methods, we demonstrate that the glucocorticoid (GC) receptor (GR) interacts with NIPBL and the cohesin complex at the chromatin level, promoting lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 73 publications
(170 reference statements)
8
22
0
Order By: Relevance
“…6 ). Surprisingly, we found that cohesin depletion, but not CTCF depletion, significantly reduces YY1 chromatin binding and slows down its target search time from 28 s to 61 s. A similar effect was also observed in SOX2 and KLF4 in the present study, as well as independently in glucocorticoid receptors by another group 91 . Furthermore, a study using high-throughput ChIP-seq analysis suggested that cohesin is critical to promote TF rebinding after mitosis 92 .…”
Section: Discussionsupporting
confidence: 89%
“…6 ). Surprisingly, we found that cohesin depletion, but not CTCF depletion, significantly reduces YY1 chromatin binding and slows down its target search time from 28 s to 61 s. A similar effect was also observed in SOX2 and KLF4 in the present study, as well as independently in glucocorticoid receptors by another group 91 . Furthermore, a study using high-throughput ChIP-seq analysis suggested that cohesin is critical to promote TF rebinding after mitosis 92 .…”
Section: Discussionsupporting
confidence: 89%
“…Now, we document a comparable reduction in interphase nuclei upon RNAPII depletion, which is most apparent at enhancers-promoter loops. This is in line with the binding of cohesin loaders at gene promoters (Busslinger et al, 2017, although the specificity of some of this data is now debated; Preprint: Banigan et al, 2022); with the fact that the loader NIPBL and unloader WAPL co-purify with RNAPII complexes (Zhang et al, 2021); as well as with recent work pointing to enhancers as cohesin-loading sites for the formation of 3D interactions (Liu et al, 2021a;Zhu et al, 2021;Rinaldi et al, 2022;Rinzema et al, 2022). Moreover, we should reconsider studies where pioneer transcription factors (like OCT4 and SOX2; Liu et al, 2021a) and chromatin remodelers (like SNF2h; Hakimi et al, 2002) affected the loading/unloading cycles of cohesin onto chromatin.…”
Section: Discussionsupporting
confidence: 59%
“…Notably, this accumulation is less if we consider an "alternative wt" model where cohesin can to bind all beads with equal probability, has a weak affinity with RNAPII, but is not allowed to co-bind promoters with it. This skews loading in favor of enhancers (Figure 4C and as suggested by recent studies; Zhu et al, 2021;Rinaldi et al, 2022;Rinzema et al, 2022). In this "wt-alt" model (Table S2), we also see increased cohesin presence and loop formation at the intragenic CTCF (Figure 4B; contact map not shown), which does not agree with our Micro-C data.…”
Section: Modeling the Interplay Between Loop Extrusion And Rnapiisupporting
confidence: 45%
“…Moreover, GR activation increases both the number and intensity of enhancer-promoter interactions of their target genes upon hormonal stimulation 20 . GR was recently described to interact with NIBL, which is responsible for cohesin loading onto DNA, localization of cohesin to GR-bound sites, and promotion of long-range genomic interactions 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Once SHRs occupy their cognate regulatory elements, a coordinated recruitment of co-regulators occurs, including chromatin remodeling factors, mediator complex, histone modifiers including histone lysine (de)-methyl transferases (KMT/KMDs), histone acetyltransferases (HATs) and ultimately RNA polymerase II (RNAPII) to drive gene transcription [11][12][13][14][15][16][17] . Altogether, SHR activation ultimately results in a large-scale transcriptional complex that loops towards targeting promoters to regulate gene expression, relying on 3D genome architectural proteins, such as the cohesin complex [18][19][20] . As a result, SHR and their interactors, together with the transcriptional machinery and 3D-genome organization proteins converge to either induce or repress specific target genes 12,17,21,22 .…”
Section: Introductionmentioning
confidence: 99%